L’image du locuteur crédible dans le discours d ’opinion - Pachocińska, Elżbieta (Studia Romanica Posnaniensia, 2001)
The trutstworthy speaker (interlocutor) presents his reasoning as based on logical deduction, although it is structured by much more complicated relations.This is because of the goal posed before the discourse in which an opinion is expressed. He tries to influence a recipient and to make him adopt a new point of view which is not based merely on logical values. To achieve this goal the speaker (interlocutor) uses argumentative structures which use procedures of natural reasoning. Autor: Pachocińska, Elżbieta.